Financial reporting of grants and assistance in government units according to IPSAS23 - محمد, صفاء احمد; حسن, ريم سعدي (Journal of Economics and Administrative Sciences, 2018)
Abstract: -The purpose of the research is to present and discuss the concept of grants and aid, with the study and analysis of the role and importance of grants and assistance on the activities of In government units, and then to determine the factors of obtaining grants and assistance, and the importance of providing accounting information in order to enhance the financial reporting of grants and assistance. The accounting system of the government and determine the areas of shortness, taking into account the failure to issue a local accounting base to determine the basis of accounting measurement and disclosure of grants and assistance to guide, and this is the starting point of the current research and so has been introduced and analysis of the application requirements IPSAS23 of D) Different accounting treatments and provision of accounting information that enhance financial reporting with application to the government unit (research sample).The purpose of the research is to present and discuss the concept of grants and aid, with the study and analysis of the role and importance of grants and assistance on the activities of economic units, and then to determine the factors of obtaining grants and assistance, and the importance of providing accounting information in order to enhance the financial reporting of grants and assistance. The accounting system of the government and determine the areas of shortness, taking into account the failure to issue a local accounting base to determine the basis of accounting measurement and disclosure of grants and assistance to guide, and this is the starting point of the current research and so has been introduced and analysis of the application requirements IPSAS23 of D) Different accounting treatments and provision of accounting information that enhance financial reporting with application to the economic unit (research sample).The study reached several recommendations, the most important of which is the need to evaluate the accounting system and provide the requirements of the accounting standards, including the transition from the monetary basis to the basis of merit and the amendment of classifications and tabulations to include the types of grants and assistance.